Code Switching and Mixing in the Lyrics of the Song “Garam dan Madu” by Tenxi, Naykilla, and Jemsii: A Sociolinguistic Study: Alih Kode dan Campur Kode dalam Lirik Lagu “Garam dan Madu” Karya Tenxi, Naykilla, dan Jemsii: Sebuah Kajian Sosiolinguistik - Fairuzah Qolbi; Endah Yustiani; Ninda Alifa; Widini Arti; Qurrota Ayu Neina (Universitas Negeri Semarang, 2025)
This study conducted an in-depth study of the sociolinguistic phenomena related to language switching and mixing in the lyrics of the popular song “Garam dan Madu” sung collaboratively by Tenxii, Naykilla, and Jemsii. Through the application of descriptive methods with a qualitative approach and the application of listening and note-taking techniques for systematic data collection, this study analyzed the sociolinguistic structures contained in all the lyrics of the song with a high level of depth. The results of the study showed four incidents of language shifting that can be classified into two main categories, namely internal language shifting and external language shifting, which provide an overview of the sociolinguistic complexity in the song's lyrics. In addition, the analysis of the phenomenon of language mixing shows the integration of languages in various forms, including words, phrases, and clauses, with a dominant tendency towards code mixing in the form of words, thus providing a more comprehensive insight into the sociolinguistic strategies used in the creation of popular song lyrics. Penelitian ini melakukan kajian mendalam terhadap fenomena sosiolinguistik yang terkait dengan peralihan dan percampuran bahasa dalam lirik lagu populer